The short-term morphological and functional changes during treatment with the Herbst appliance - Kuroda, Takayuki; Hiyama, Shigetoshi; Ishiwata, Yasuo; Ono, Takashi (The Journal of Japanese Society of Stomatognathic Function, 1996)
The purpose of this study was to examine functional muscular adaptation through analysis of the shortterm morphological and functional changes induced by the use of the Herbst appliance. Four patients with Angle Class II Division 1 malocclusions, age range 9y6m-lly2m were chosen as subjects. Lateral cephalograms were taken to evaluate morphological changes. The electromyographic (EMG) activity of the inferior head of the lateral pterygoid (ILpt) muscle was recorded with an intraoral surface electrode. A similar pattern of cephalometric changes was observed in all patients. Immediately after wearing the appliance, the condyles of all patients translated antero-inferiorly and the EMG activity of the ILpt muscle was significantly increased. After several months, the condyles of three patients were still positioned antero-inferiorly as compared to their original positions; however, the EMG activity of the ILpt muscle had decreased to the pre-treatment level in all patients. Just after removal of the appliance, the EMG activity of the ILpt muscle significantly increased in response to minor morphological changes. Two weeks after removal of the appliance, the EMG activity decreased again to the pre-treatment level. These data indicate that the functional muscular adaptation is established within a short period, prior to compensatory morphological adaptation.